2014
DOI: 10.1037/neu0000050
|View full text |Cite
|
Sign up to set email alerts
|

Working memory and intraindividual variability as neurocognitive indicators in ADHD: Examining competing model predictions.

Abstract: The current findings question the role of RT variability as a primary neurocognitive indicator in ADHD and suggest that ADHD-related RT variability may be secondary to underlying deficits in CE working memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 72 publications
3
55
4
1
Order By: Relevance
“…[5][6][7] Neuropsychological tests evaluate attention, memory, perception, intelligence, processing speed, resistance to distraction, as well as verbal skills. 25,31 The present findings showed that the neuropsychological performance of children and adolescents has a direct predictive influence on the severity of inattention and hyperactivity symptoms as assessed by participant caretakers.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Neuropsychological tests evaluate attention, memory, perception, intelligence, processing speed, resistance to distraction, as well as verbal skills. 25,31 The present findings showed that the neuropsychological performance of children and adolescents has a direct predictive influence on the severity of inattention and hyperactivity symptoms as assessed by participant caretakers.…”
Section: Discussionmentioning
confidence: 99%
“…8,13,[32][33][34][35] The behavioral neuroenergetics theory postulates neuronal energy insufficiency as a result of inadequate production of lactate by astrocytes. 32,34 State (vigilance) regulation theories hypothesize that the core deficit in ADHD is impaired regulation of activation state (arousal). 33,36 Some symptoms are attributed to dysfunctional fluctuations in arousal (e.g.…”
Section: Neurobiologymentioning
confidence: 99%
“…13,35 One variant of this theory specifically implicates inconsistent suppression of default mode network (DMN) activity. 34 Impaired bottom-up (limbic) regulation of reward-related processing has also been proposed. 13,33,35 Multiple pathway theories postulate that individually variable deficits in multiple core functions (e.g.…”
Section: Neurobiologymentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The presence of neuropsychological impairments in patients with ADHD relative to control subjects is corroborated by studies involving neuropsychological assessment, especially of the executive functions. [5][6][7] However, short-term memory is the only cognitive function to have shown a specific association with the severity of hyperactivity symptoms. 8 There is no consensus in the literature regarding the association between the clinical presentation of ADHD and specific patterns of cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%